DISTINCTIVE FEATURES OF USING DIGITAL EDUCATIONAL TECHNOLOGIES IN TEACHING PHYSICS AT ACADEMIC LYCEUMS OF THE INTERNAL AFFAIRS SYSTEM - Najmiddinov Murat Kamolovich (International Scientific and Current Research Conferences, 2026)
This article analyzes the theoretical and methodological foundations, didactic potential, and specific organizational and pedagogical features of using digital educational technologies in teaching physics at academic lyceums within the system of the Ministry of Internal Affairs. In particular, the study highlights mechanisms for improving physics education through simulation-based modeling, virtual laboratories, digital measurement systems, artificial intelligence–driven adaptive platforms, and STEAM integration. Considering the professional orientation, disciplinary environment, and safety requirements characteristic of academic lyceums of the internal affairs system, an effective model for the implementation of digital technologies in physics instruction is proposed.